2010
DOI: 10.1002/acr.20183
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of varicella vaccine in patients with juvenile rheumatic diseases receiving methotrexate and corticosteroids

Abstract: Objective. To evaluate the safety and immunogenicity of varicella vaccine (VV) in susceptible patients with juvenile rheumatic diseases receiving methotrexate and corticosteroids. Methods. Twenty-five patients with juvenile rheumatic diseases (ages 2-19 years) and 18 healthy children and adolescents (ages 3-18 years) received a single dose of VV. All 25 patients were receiving methotrexate; 13 were also receiving prednisone and 5 were also receiving other disease-modifying antirheumatic drugs. None of the vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 18 publications
1
78
0
3
Order By: Relevance
“…Moreover, no worsening in the activity of rheumatic diseases has been verified. 24 Another Brazilian study reported the practice of vaccination against yellow fever in seventy adult patients with rheumatic diseases, with mild adverse events observed in 22% of patients. 25 In conclusion, the practice of immunization surveillance by pediatric rheumatologists is low, especially after the first visit, possibly due to lack of efficacy and safety of vaccines in children and adolescents with rheumatic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no worsening in the activity of rheumatic diseases has been verified. 24 Another Brazilian study reported the practice of vaccination against yellow fever in seventy adult patients with rheumatic diseases, with mild adverse events observed in 22% of patients. 25 In conclusion, the practice of immunization surveillance by pediatric rheumatologists is low, especially after the first visit, possibly due to lack of efficacy and safety of vaccines in children and adolescents with rheumatic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The studies [14,15] have shown that vaccination of patients with rheumatoid arthritis against influenza, diphtheria, tetanus, and meningococcal infection has not resulted in the clinical setting deterioration. However, simultaneous use of supporting immunosuppressive therapy at average age doses was found not to inhibit the production of protective antibodies when vaccinated against diphtheria [15,16], whooping cough [15,17], hepatitis В [15,18], influenza [15,19].…”
Section: сLinical Medicinementioning
confidence: 99%
“…89 Nevertheless, varicella vaccination is contraindicated in patients receiving glucocorticoids at prednisone equivalent doses of 2 mg/kg/day or 20 mg/ day for >14 days. 90 Pileggi et al 83 evaluated the immunogenicity and tolerance of the VZV vaccine in one study of 25 sensitive children with RD and 18 healthy controls. All patients were receiving MTX, 13 were also receiving prednisone and five others were using DMARDs.…”
Section: Varicella Vaccinesmentioning
confidence: 99%